REAL-TIME SCHOOL MONITORING PROGRAM IN DISTRICT QUETTA AND ITS IMPACT ON SECONDARY SCHOOL TEACHER’S PERFORMANCE - Hina Hashmi; Dr Victoria Joseph; Shazma Nandawani; Syed Muhammad Ishaq (International Journal of Contemporary Issues in Social Sciences, 2023)
The objective of this research is to examine the effects of the Real-Time School Monitoring System (RTSMS) on secondary and upper secondary educational institutions in the city of Quetta. The implementation of the system was initiated by the Government of Baluchistan in partnership with the Baluchistan Education Project (BEP), which is supported by the World Bank. The primary objective of this initiative is to improve the quality of education, with a specific focus on the public sector. This study examines the deployment of the Real-Time School Monitoring System (RTSMS) in the Quetta district, with a specific emphasis on its impact on teacher performance and the issue of absenteeism. The data collection included the distribution of questionnaires to a sample of 320 secondary school principals and teachers. This research used a correlational design. The use of quantitative analysis using SPSS software yielded a robust positive correlation of 76% and a regression coefficient of 75%, indicating a significant association between the variables. Significantly, the observed impact of 58% serves to emphasize the effectiveness of RTSMS in enhancing teacher attendance by more than 30% and promoting a favorable learning environment. This underscores the potential of RTSMS to contribute to broader improvements in education, including infrastructure, teacher-parent communication, and student attendance.